Turkish validation of a resilience scale from older people’s perspectives: resilience scale for older adults - Seher Palanbek Yavaş; Caner Baysan (PeerJ)
Background As the global population ages and life expectancy increases, older adults encounter challenges like chronic illnesses and losing loved ones; resilience is crucial for adapting to these difficulties. This study aims to culturally and linguistically adapt the psychological resilience scale designed for older adults to the Turkish context. Methods This methodological study included 566 individuals aged 65 and older. All participants completed the Resilience Scale for Older Adults, the Perceived Stress Scale, the Geriatric Depression Scale, and the Quality of Life in Older Adults Scale—Short Form. Construct validity was assessed through confirmatory and exploratory factor analyses, while convergent and discriminant validity were evaluated through the correlation of the scales. Reliability was determined using internal consistency and the split-half method. Results The scale retains its original structure with 33 items and four sub-dimensions (Intrapersonal, Interpersonal, Spiritual, and Experiential). The content validity index of the scale is 0.98, with item loadings ranging from 0.406 to 0.947, according to exploratory factor analysis. Confirmatory factor analysis indicates good fit indices. Convergent validity is supported by a strong positive correlation (r = 0.657, p < 0.001) between the Resilience Scale for Older Adults and the Quality of Life in Older Adults Scale—Short Form. Reliability measures include a Cronbach’s alpha internal consistency coefficient of 0.93 and a Guttman split-half reliability coefficient of 0.723. Conclusion The results show that the Turkish version of the Resilience Scale for Older Adults is a valid and reliable measurement tool.